Interpreting practices in health care : an investigation of differences across trained and untrained interpreters in initial assessment interviews, within the field of Speech-Language and Hearing Therapy - Fisch, Mandy (Department of Health and Rehabilitation Sciences, 2014)
Bibliography: leaves 168-181.